Adaptation to active learningmethodologies in nursing: a study fromthe teaching perspective - Abselam-Ali, Karima (2025)
Introduction: The implementation of the European Higher Education Area (EHEA) requires the adoption of Active Learning Methods (ALMs) to promote meaningful and reflective learning. This is particularly beneficial in nursing education, as it enhances students’ clinical preparation. It also demands pedagogical renewal and thoughtful reflection on methodological changes from the teaching perspective. Objective: To describe the key aspects that nursing educators consider important for implementing ALMs in their teaching. Method: A qualitative study with a hermeneutic phenomenological design was conducted, involving 10 semi-structured interviews with nursing degree instructors at the University of Granada (Spain). Results: The main theme was “Adaptation to active learning methods in nursing,” with subthemes including training experiences, use of lectures, meanings and integration of ALMs, and teaching perspectives. Discussion: Although there is institutional interest in enhancing student engagement and critical thinking, ALMs require time, training, and greater support. Conclusions: Continuous professional development and institutional investment are essential for the successful integration of ALMs into teaching.